Knowledge sharing framework for Sustainable Value Planning in Malaysian public construction projects / Faudzi Muhammad - Muhammad, Faudzi (Institute of Graduate Studies, UiTM, 2017)
Malaysia is pursuing the status of a high-income nation by the year 2020. In tight economic conditions, the government has to improve the value of public spending through increasing its sustainability with the lowest possible investment. Although construction projects contribute to the country’s economic growth and fulfil social needs, they also contribute to environmental deterioration. Besides that, construction projects in Malaysia are criticised for low productivity and failure to achieve client satisfaction. Due to these reasons, the government has introduced the Green Growth concept to promote sustainable development for public projects and Value Management (VM) to improve the projects’ value for money. Value Planning (VP) is the front end of VM, conducted during the early project planning stage. Due to various advantages of integrating sustainability considerations during the early stages, VP is the best platform to achieve value for money and project sustainability at the same time. Sustainable Value Planning (SVP) is a concept that integrates both value for money and sustainability targets in a single mechanism. Effective knowledge sharing is the key driver for SVP. Despite the recognition of the importance of effective knowledge sharing within VP, its contribution in nurturing sustainability integration into the practice remains unclear. Thus, this study is conducted with the aim of developing the Knowledge Sharing Framework For Sustainable Value Planning. This framework explains the constructs involved and their relationships during the SVP in the context of knowledge sharing for Malaysian public construction projects. This study was conducted based on the philosophy of pragmatism and adopted the abductive approach…